Sexting and Displacement of Pride in a Contemporary Digitised World - Inobemhe, Kelvin; Usman, Momoh; Modeyin, Oluwatobi (Journal of Contemporary Issues in Media & Communication (JCIMC), 2025)
This study focuses on the impact of sexting on the sense of pride among digital technology users who communicate virtually anything with their digital devices such as the mobile phones, laptop or tablets. Interactions across digital platforms involve the exchange of pictures, videos and messages generally referred to as “sexts.” The researchers relied on secondary data sources and identified both positive and negative dimensions of sexting. Findings of the study demonstrated that sexting affects individuals’ sense of pride through vulnerability, exposure, objectification, unrealistic expectations, regret and shame. However, some positive outcomes of sexting are affirmation and exploration of one’s sexuality, self-expression, intimacy as well as connections between partners involved in such communications. On the other hand, the researchers noted glaring negative effects prominent of which is the issue of diminishing self-esteem particularly when sexting is non-consensual. The coercion to sext can lead to feelings of powerlessness especially among those categorised as “victims” of the act. Gender and social dynamics also play a significant role in sexting. The researchers concluded that there is a correlation between digital communication and personal identity as acts such as sexting conducted in digital space can have dire consequences for an individual’s sense of pride or self-esteem. It is, therefore, recommended, among several others, that digital literacy and education be promoted among young persons to teach them about risks and responsibilities associated with sexting in the digital age.